Impact of gut microbiota on nonalcoholic fatty liver disease: insights from a leave-one-out cross-validation study - Pan, Tongtong; Su, Lihuang; Zhang, Yiying; Yi, Fangfang; Chen, Yongping (Frontiers in Microbiology, 2024)
Introduction: Enteric dysbacteriosis is strongly associated with nonalcoholic fatty liver disease (NAFLD). However, the underlying causal relationship remains unknown. Thus, the present study aimed to investigate the relationship between gut microbiota and NAFLD using Mendelian randomization (MR) and analyze the target genes potentially regulated by specific microbiota.Methods: Bidirectional two-sample MR analysis was performed using inverse variance weighted (IVW) supplemented by MR-Egger, weighted median, simple mode, and weighted mode methods.Data were pooled from gut microbiota and NAFLD association studies. The least absolute shrinkage, selection operator regression, and the Support Vector Machine algorithm were used to identify genes regulated by these intestinal flora in NAFLD. The liver expression of these genes was verified in methionine choline-deficient (MCD) diet-fed mice.Results: IVW results confirmed a causal relationship between eight specific gut microbes and NAFLD. Notably, the order Actinomycetales, NB1n, the family Actinomycetaceae, Oxalobacteraceae and the genus Ruminococcaceae UCG005 were positively correlated, whereas Lactobacillaceae, the Christensenellaceae R7 group, and Intestinibacter were negatively correlated with NAFLD onset. In NAFLD, these eight bacteria regulated four genes: colony-stimulating factor 2 receptor β, fucosyltransferase 2, 17-beta-hydroxysteroid dehydrogenase 14, and microtubule affinity This is a provisional file, not the final typeset article regulatory kinase 3 (MAPK3). All genes, except MARK3, were differentially expressed in the liver tissues of MCD diet-fed mice.Discussion: The abundance of eight gut microbiota species and NAFLD progression displayed a causal relationship based on the expression of the four target genes. Our findings contributed to the advancement of intestinal microecology-based diagnostic technologies and targeted therapies for NAFLD.